Aerated Drilling Optimization in Geothermal Well Drilling in Field “X” Cluster “Y” - Raka Aditya Pratama; Astra Agus Pramana; Bambang Kustono (Journal of Earth Energy Science, Engineering, and Technology, 2018)
Aiming for productive fault in Suban Agung Rim, Field X Cluster Y Bengkulu Province, Indonesia, PT Pertamina Geothermal Energy (PGE) drilled some wells to discover the potential awaited. However there are challenge awaits each meter ahead especially in reservoir sections where loss circulation is expected. Knowing the risk, PGE decided to drill the well utilizing aerated drilling. The method has known for decades to be the most effective approach in dealing loss circulation. The method applies certain value of compressed air to be injected in fluid stream, so bubbling process can be achieved in order to reduce the mud weight. The method has benefit to maintain ROP and minimize the risk for pipe get stuck due to poor hole cleaning in fractured formation. There are three wells drilled in Field X Cluster Y which has the same problem in 9-7/8” section; all experienced stuck pipe while drilling. During the process aerated drilling was utilized, however it was not sufficient. This paper will discuss and explain on how the occurrence happened and what to do next in similar condition to avoid the problems.